PERAN MEDIA CENTER DALAM MENGELOLA DAN MEMBENTUK CITRA KANDIDAT DIA PADA PEMILIHAN WALIKOTA MAKASSAR 2013 - Syahrir Soleman; Hasrullah Hasrullah; Muhammad Iqbal Sultan (KAREBA : Jurnal Ilmu Komunikasi, 2015)
Abstract DIA Media Center is the central of planning and managing imaging messages a candidate on Election Mayor and Vice Mayor of Makassar in 2013. The aim of this research was to find out the role of media center in managing and shaping the image of DIA candidates and communication strategy used by media cent er in the election of mayor and vice mayor of Makassar in 2013. The research used descriptive method with qualitative approach conducted in Makassar City, South Sulawesi Provincee consisting of 8 informants who were all the team members of DIA media center. The data were obtained through observation and interview. They were analyzed using qualitative analysis. The results of the research indicate that media center controls production and dissemination process of imaging messages through printed media such as newspapers, outdoor advertisements, car stickers, and small format media, electronic media such as television and radio, and social media such as facebook, twitter, youtube, and websites. Media center is also used to deaden and neutralize negative campaign and black campaign from political opponents. Communication planning is done through communication strategy through the stages of setting the goals, analyzing the audience, developing the message, choosing communication media, disseminating message through individual communication, group communication, and mass communication, and doing gradual evaluationAbstrak Media Center DIA merupakan pusat perencanaan dan pengelolaan pesan pencitraan kandidat pada Pemilihan Walikota dan Wakil Walikota Makassar 2013. Penelitian ini bertujuan untuk mengetahui peran media center dalam mengelola dan membentuk citra kandidat DIA dan strategi komunikasi yang digunakan media center pada pemilihan Walikota dan Wakil Walikota Makassar pada tahun 2013. Penelitian ini dilakukan di Kota Makassar, Provinsi Sulawesi Selatan. Jumlah informan 8 orang yang kesemuanya merupakan bagian tim media center DIA. Pengumpulan data dilakukan dengan observasi dan wawancara. Data dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa media center mengontrol proses produksi dan penyebaran pesan pencitraan melalui media cetak seperti koran, iklan luar ruang, stiker mobil, media format kecil, dan juga media elektronik seperti televisi, radio serta media baru seperti media sosial facebook, twitter, youtube, website. Media center juga digunakan untuk meredam dan menetralkan kampanye negative dam kampanye hitam dari lawan politik. Perencanaan komunikasi dilakukan melalui strategi komunikasi dengan tahapan menetapkan tujuan, menganalisis khalayak, menyusun pesan, memilih media komunikasi, dan menyebarkan pesan melalui komunikasi individu, komunikasi kelompok, dan komunikasi massa, kemudian melakukan evaluasi secara bertahap.